An Upgraded Transverse Electromagnetic Parallel Plates for Dielectric Measurement - S. K. Yee; R. Padu; C. K. Sia; X. T. I. Ngu; S. H. Dahlan; M. A. Azlan (Universitas Ahmad Dahlan, 2017)
A new version of transverse electromagnetic parallel plates with irregular plates’ width and plate separation has been developed for dielectric measurement. The separations between the plates are supported by four rectangular Teflon block and 1 mm of groove is proposed at the center of the upper plate to maintain the measurement repeatability. The groove enables the samples which are slightly higher than 2 cm to be fitted well between the plates without introducing extra force to the plates. Theperformance of both parallel plates has been compared in the frequency range from 100 MHz to 1.1 GHz. It is found that the upgraded parallel plate offers better return loss and insertion loss above 500 MHz compared to the previous parallel plate. It is reported from this work that the return loss of the parallel plate must be lower than -15 dB in order to achieve accurate dielectric constant. However, the insertion loss of the parallel plates does not influence the real permeability significantly. The upgraded TEM parallel plateproduces a consistent reading with a standard deviation of less than 0.05 above frequency 200 MHz. The dielectric measurement of Polypropylene (PP) has proven the capability of this upgraded TEM parallelplate.